Percepção da cultura de segurança do paciente pelos enfermeiros de Unidades de Terapia Intensiva - Lima Neto, Alcides Viana de (2017)
Safety culture, understood as the product of values and attitudes at an organizational environment, is an important factor in the context of safe care at health services. Understanding it is necessary so that professionals can adopt strategies to ensure patient safety in the most diverse scenarios of care practice. Thus, the object of this study was the safety culture in the context of intensive care units (ICUs), in nurses’ opinions, since they are inserted in this environment and responsible for managing actions related to care. Therefore, the objective was to analyze the perception of the patient safety culture in the ICU from nurses’ perspective. This is a descriptive and exploratory study with a mixed approach. The study scenario consisted of four general ICUs from Natal/RN, Brazil, which present similar characteristics, but from different hospital services and with public and private management. The sample consisted of 45 nurses. Data collection was performed by instrument filling with sociodemographic data, semi-structured interview with open questions about the subject and filling of the questionnaire entitled Research of Patient Safety at Hospitals, from April to June 2017. Interviews were analyzed using the Iramuteq software, and the quantitative data, the Statistical Package for the Social Sciences software through descriptive statistical analysis. The Research Ethics Committee of the Federal University of Rio Grande do Norte approved the study in its ethical and methodological aspects with certificate of presentation for ethical appreciation number 62818516.7.0000.5537. The interviews showed nurses’ understanding of patient safety and its promotion actions in the intensive care unit, as well as the aspects that facilitate and/or hinder it, with emphasis on the weaknesses of the structural resources. Regarding safety culture, the dimensions related to teamwork, organizational learning and openness to communications obtained the best percentages of positive responses. Regarding weaknesses and opportunities for improvement, the emphasis was on non-punitive responses to mistakes and personal dimension. The ones with the highest results classified as neutral answers were teamwork by the hospital units and frequency of event reports. With this, the analyzed ICU nurses perceived the strong presence of a punitive culture and the weaknesses of resources that are essential for patient safety. Thus, managers need to look at these issues in order to contribute to the reduction of these critical nodes and to implement safety culture.